2018
DOI: 10.16943/ptinsa/2018/49347
|View full text |Cite
|
Sign up to set email alerts
|

Central Dogma, Selfish DNA and Noncoding RNAs: A Historical Perspective

Abstract: Major discoveries like the one gene-one enzyme hypothesis, demonstration of DNA as the genetic material and finally the elucidation of the double helical structure of DNA in 1940s and early 1950s set the stage for emergence of molecular biology. Parallel cell biological studies during this period also indicated a correlation between rate of protein synthesis in a cell and the amount of cytoplasmic RNA. Following the proposal of George Gamow, a physicist, about the triplet genetic code and possible involvement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…Therefore, a substantial population of RNAs remains as noncoding RNAs (Abascal et al, 2020). Previously these noncoding RNAs were considered as transcriptional noise but eventually, several reports have shown that they have significant roles in various processes like pre-rRNA transcription, processing, and maturation (Lakhotia, 2018;Yan et al, 2019), regulation of chromosomal architecture and chromatin remodeling (Yao et al, 2019). Noncoding F I G U R E 1 Molecular regulation of hypoxic responsive genes under both normoxic and hypoxic conditions.…”
Section: Long Noncoding Rnas and Hypoxiamentioning
confidence: 99%
“…Therefore, a substantial population of RNAs remains as noncoding RNAs (Abascal et al, 2020). Previously these noncoding RNAs were considered as transcriptional noise but eventually, several reports have shown that they have significant roles in various processes like pre-rRNA transcription, processing, and maturation (Lakhotia, 2018;Yan et al, 2019), regulation of chromosomal architecture and chromatin remodeling (Yao et al, 2019). Noncoding F I G U R E 1 Molecular regulation of hypoxic responsive genes under both normoxic and hypoxic conditions.…”
Section: Long Noncoding Rnas and Hypoxiamentioning
confidence: 99%
“…Heterochromatin variability could indicate the polymorphism rates in parthenogenetic clonal populations. There is a growing understanding that heterochromatin rearrangement and its tethering can be related to subtle and substantial phenotypic effects [65,66]. The identification of CR1-rng (LINE) in heterochromatin could provide insight into the mechanism of heterochromatin block variability.…”
Section: Lines In Eukaryote Genomes and Transcriptomesmentioning
confidence: 99%
“…Protein synthesis is a crucial phase for any living organism; therefore, any phenomenon affecting any of the steps involved in such a crucial process could jeopardize life itself or cause severe disorders. Protein synthesis, in the classical vision of the central dogma, consists of two steps: transcription and translation (Figure 1) [1,2,3]. Therefore, any strategy aiming at correcting miscarried protein syntheses should intervene before the synthetic process is completed.…”
Section: Introductionmentioning
confidence: 99%